Identification and mapping of adventure tourism resources in Sohra Civil Sub-Division areas, Meghalaya/ Londoner Murphy Sohtun - Sohtun, Londoner Murphy (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
The main objective of this paper is to identify and map the adventure tourism resources having the potential to be developed in the Sohra civil sub-division areas of Meghalaya. The study firstly identified the adventure tourism resources and then mapped them accordingly. Interview and open discussions were held with various tourism stakeholders comprising adventure operators, state government officials, tour guides and local headmen to familiarise with the presence of adventure tourism resources in the area after which field visits were undertaken for verification. A matrix was used for the presentation and a better understanding of the identified adventure tourism resources. In total, nine adventure tourism resources falling under Sohra civil sub-division were identified as having the potential to be developed for adventure tourism. Each adventure resource was mapped against those sites/villages where adventure tourism could be carried out. The findings indicated that areas falling under Sohra civil sub-division have immense potential for adventure tourism due to varied adventure tourism resources. However, there is much more to explore new adventure resources in the area through a planned and systematic approach for the development of adventure tourism.